2019
DOI: 10.1007/s40263-019-00686-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychostimulants/Atomoxetine and Serious Cardiovascular Events in Children with ADHD or Autism Spectrum Disorder

Abstract: Background Psychostimulants and atomoxetine have been shown to increase blood pressure, heart rate, and QT interval in children and adolescents; however, based on current literature, it is unclear if these "attention-deficit/hyperactivity disorder (ADHD) medications" are also associated with serious cardiovascular (SCV) events. We addressed this question in commonly exposed groups of children and adolescents with either ADHD or autism spectrum disorder (ASD). Methods Using commercial (years 2000-2016) and Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…In contrast, the increased risk of MI or stroke was not found to be significantly higher in those who recently started stimulants or atomoxetine in half a million participants . Moreover, most studies did not find any association between atomoxetine and MI or stroke (Holick et al, 2009;Schelleman et al, 2012;Houghton et al, 2020). However, stimulants/atomoxetine might increase the risk of a transient ischemic attack in adults (Holick et al, 2009) which was not observed for children.…”
Section: Myocardial Infarction Aortic Dissection and Strokementioning
confidence: 99%
“…In contrast, the increased risk of MI or stroke was not found to be significantly higher in those who recently started stimulants or atomoxetine in half a million participants . Moreover, most studies did not find any association between atomoxetine and MI or stroke (Holick et al, 2009;Schelleman et al, 2012;Houghton et al, 2020). However, stimulants/atomoxetine might increase the risk of a transient ischemic attack in adults (Holick et al, 2009) which was not observed for children.…”
Section: Myocardial Infarction Aortic Dissection and Strokementioning
confidence: 99%
“…Elevated blood pressure and heart rate have been reported in patients with atomoxetine therapy ( 101 ). However, the effects of most patients on the cardiovascular system have no clinical significance ( 101 , 128 , 129 ). Hammerness et al ( 130 ) found a statistically significant increase in heart rate in 6- and 7-year-old children with ADHD who received atomoxetine compared with placebo ( p < 0.001).…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Of note, the use of stimulants did not cause any significant changes in adverse cardiovascular events in children and adults [38] , [44] , [54] . Despite non-pathological increases in BP, HR, and QT interval, because increased BP, HR, and QT interval are associate with cardiovascular morbidity and mortality during adulthood so pediatric patients treated with ADHD medication need to be monitored for HR and BP, closely and regularly.…”
Section: Discussionmentioning
confidence: 81%
“…Reports related to sudden deaths of patients, mainly children, treated by these drugs have raised the question of whether these medications increase the risk of cardiovascular events [37] . On the other hand, numerous massive cohort studies have not demonstrated any increased risk of life-threatening cardiovascular events among children treated by stimulants compared with the general population [38] . However, sudden death remains an extremely rare event and not be attributed to methylphenidate as there is no clear evidence supporting this association [39] .…”
Section: Discussionmentioning
confidence: 95%